TRANSFORMASI ‘NEGOSIASI’ SEBAGAI MEKANISME PENYELESAIAN SENGKETA ALTERNATIF DI INDONESIA - Djajadibrata, Tara Kartika (PT Wahana Global Education, 2025)
Negotiation is a method of resolving conflicts outside the courts that has long been used in legal practice and social life in Indonesia. Over time, negotiation has evolved from an informal form based on local wisdom to a legally recognized mechanism within the national dispute resolution system. This study aims to trace this transformation across various periods, from the colonial period to the present modern era. The research problem focuses on how the legal and institutional legitimacy of negotiation has changed, as well as the challenges and opportunities faced in its implementation. Using a descriptive-analytical approach within a normative legal research framework, this paper reveals that although negotiation has been legally regulated in legal instruments such as Law No. 30 of 1999, its existence still requires further scrutiny, and its implementation still faces structural, regulatory, and social obstacles. Therefore, strengthening the legal framework, adapting technology through ODR, and increasing public understanding are key to optimizing the function of negotiation as an efficient, inclusive, and equitable dispute resolution mechanism